Digital divide: how is Indonesian public service affected? - Sutrisno, Edy; Silitonga, Mala Sondang; Yusuf, Rima Ranintya; Nugroho, Alih Aji (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study clearly sets out how much the extent of the digital divide affects e-government services being adopted by Indonesia. Such inequality in access and competence of nations in digital technology is one of the great stumbling blocks erected in the way of the Indonesian government to carry out various programs. The research methodology in this paper is largely qualitative, with a mixed method of case study and literature review of the relevant online media to facilitate a description of the digital divide that translates into the use or nonuse of digital public services. This research seeks to identify trends and relationships that may bind together policy contexts and the digital divide. The data for this research were collected through the analysis of secondary data from a wide range of data sources, including the Indonesia Digital Literacy Index survey 2022 and BPS data, both from the service provider and the service user. The findings of the research point to a very low level of digital literacy in Indonesia, especially in terms of digital security. Mainly, the digital divide complicates the social exclusion of older generations, yet, in principle, digital technologies can help people in the older generation live better lives. The core argument of this report is that cutting the digital divide requires investment, training, and leadership based on trust from the concerned parties to see there is an open fair access to digital services.